The Click and Go Decision Tool: Towards Inclusive and Accessible Visual Literacies - Asensio, Mireia; Young, Clive; Little, Ross; Cuttle, Mary (Proceedings of the International Conference on Networked Learning, 2004)
The increasing development of digital rich resources promises and exciting opportunity to transform video and audio media into mainstream networked learning. The use of visual and audio literacies can inspire us to express ideas not readily available in written form, and in this way, it can enable different ways of representation and access to a wider and more dispersed student population. This paper will describe the concept of ‘visual literacy’ and the notion of ‘inclusive’ technology. Visually rich resources might perhaps bring more access, control and choice to networked learning events. However this apparently inclusive technology might be perceived as a barrier to ensure accessibility for users who have sensory disabilities. The JISC Click and Go: Access for All project (2003) has explored, through the use of inquiry groups and questionnaires, practitioners’ perceptions, understandings and experiences around the area of accessible digital video and audio. This paper explores current practice and introduces a decision tool intended to provide a practical route to clarify intentions and requirements through the use of questions and possible answers.